Nature of manganese species in Ce1-xMnxO2-delta solid solutions synthesized by the solution combustion route - Murugan, B.; Ramaswamy, A. V.; Srinivas, D.; Gopinath, Chinnakonda S.; Ramaswamy, V. (Chemistry of Materials, 2005)
A series of manganese-cerium oxide composites with Mn concentrations in the range of 1-20 mol % in ceria was prepared by the solution combustion technique using urea as fuel. The nature, type, and oxidation state of Mn species in ceria were investigated by X-ray diffraction (XRD), diffuse reflectance UV-visible spectroscopy, electron paramagnetic resonance (EPR), X-ray photoelectron spectroscopy, and temperature-programmed reduction techniques. The study reveals that the method of preparation significantly influences the type of manganese species in ceria. Wet-impregnation, coprecipitation, and solid-state synthesis techniques lead to clustered MnOx-like species in the ceria matrix, while the present method of preparation (solution combustion route) yields a highly dispersed form of Mn species. In the reported series of samples, Mn is present mainly in +2 and +3 oxidation states and there is no evidence for the presence of Mn 41 species. Powder X-ray diffraction studies at variable temperatures (298-1323 K) indicate the formation of Ce1-xMnxO2-delta Solid solutions. No separate MnOx-type phase was detected even at 1323 K. EPR studies reveal that the isolated Mn2+ and Mn2+ species are present in at least three different structural locations: species A, Mn ions in ceria-lattice defect sites; species B, Mn ions in framework Ce4+ locations; and species C, Mn ions in interstitial locations and at the surface of ceria. The Mn3+ ions in ceria exhibit a facile reduction and reoxidation behavior when exposed to dry hydrogen and subsequently to air at elevated. temperatures. A highly dispersed state of Mn3+ and Mn2+ in ceria, facile redox behavior, and a synergistic Mn-ceria interaction are some of the unique properties of this material prepared by the solution combustion procedure.